Gestational age-specific hematological patterns in preterm infants following necrotizing enterocolitis. (12th December 2022) - Garg, Parvesh Mohan; Paschal, Jaslyn L.; Ware, Jennifer; Hobart, Haley L.; O'Connor, Anna; Ansari, Md Abu Yusuf
Abstract: Objective: To investigate gestational age (GA) specific hematological and transfusion response patterns in preterm infants following necrotizing enterocolitis (NEC) Design: A retrospective study comparing hematological/transfusion information in three GA groups' infants: Group A ≤ 28 weeks. Group B 28–32 weeks, Group C > 32 weeks following necrotizing enterocolitis. Results: Group A infants responded with significantly higher WBC count, thrombocytopenia, higher absolute neutrophil, and higher absolute monocyte and lower absolute lymphocyte counts following NEC onset, received more blood transfusions before NEC onset (59.8 versus 30.0%; p = .007), and had higher odds of surgical NEC (OR 3.39 [95% CI 1.19–10.38]; p = .02) than group C. One unit increase in absolute lymphocyte count on the day, and 24 h following NEC was significantly associated with lower surgical NEC odds than groups C. Conclusion: The infant's in-group A had significantly different hematological response patterns following NEC than infants with higher gestational age (groups B and C).